Charlie Numbers and the man in the moon - Mezrich, Ben, 1969-; Mezrich, Tonya (Simon & Schuster Books for Young Readers, 2017)
When sixth-grade mathematical genius Charlie Lewis is recruited to recover moon rocks taken from NASA's vaults, the Whiz Kids enter a paper airplane contest hosted by the suspect's company.